2018
DOI: 10.1021/acscatal.8b01131
|View full text |Cite
|
Sign up to set email alerts
|

Trace Level Co–N Doped Graphite Foams as High-Performance Self-Standing Electrocatalytic Electrodes for Hydrogen and Oxygen Evolution

Abstract: The development of eco-friendly electrocatalysts with high performance and low cost for hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) is significant for renewable energy storage. Here, trace level (0.11−0.18 wt %) Co−N doped graphite foam (Co−N/GF) was reported to work as a bifunctional high-performance and self-standing electrode for both HER and OER in alkaline electrolyte. The catalytic activities of Co−N/GFs with different annealing temperatures (600, 700, 800, 900, and 1000 °C) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…As displayed in Fig. 4a,c, the dominant peaks located at 781.4 and 797.6 eV were ascribed to Co 3+ 2p 3/2 and 2p 1/2 , respectively, and the binding energy at 782.6 eV was assigned to Co 2+ 2p 3/2 24,39,42,50 . It was obvious that in CFHC the XPS peaks at 781.4 eV for Co 3+ were enhanced while the peak corresponding to Co 2+ at 782.6 eV was decreased (Fig.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…As displayed in Fig. 4a,c, the dominant peaks located at 781.4 and 797.6 eV were ascribed to Co 3+ 2p 3/2 and 2p 1/2 , respectively, and the binding energy at 782.6 eV was assigned to Co 2+ 2p 3/2 24,39,42,50 . It was obvious that in CFHC the XPS peaks at 781.4 eV for Co 3+ were enhanced while the peak corresponding to Co 2+ at 782.6 eV was decreased (Fig.…”
Section: Resultsmentioning
confidence: 90%
“…Therefore, it is appealing but highly challenging to design and construct earth-abundant and low-cost electrocatalysts for OER and UOR. Up to now, various noble-metal-free catalysts have been developed, such as metal oxides 16,17 , metal hydroxides 1820 , metal chalcogenides 21,22 , metal phosphides 23 , metal nitrides 24 , and metal carbides 25 , etc. However, the performance of these reported materials as a bifunctional electrocatalyst both for OER and UOR are far from the industrial utilization.…”
Section: Introductionmentioning
confidence: 99%
“…Benefiting from excellent tuneable surface physical chemical properties, thermal stability and corrosion resistance against acid and alkali, carbon nanomaterials have been widely applied in constructing carbon composite electrocatalysts. [21][22][23] Due to the strong metal-support interactions, support materials usually play a vital role in optimising the local electronic and geometric structures of metal sites. 24,25 In the development of support materials, the tuning and stabilising effect over the catalytic sites should be considered.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, heteroatom doping was effective on the increase of active sites and regulation of electron distribution [ 18 , 19 , 20 , 21 , 22 ]. It has been demonstrated that co-doping multi elements with different electronegativity can remarkably improve the performance of graphene due to the positive synergistic effect of heteroatoms [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Ci et al [ 35 ] simultaneously doped graphene with nitrogen and loaded cobalt to obtain Co/NG catalyst by heat treatment.…”
Section: Introductionmentioning
confidence: 99%